Comparison of Acid Hydrolyses of 4 Kinds Starch - Sukoncheun Sringam, (Agriculture and Natural Resources, 1994)
Hydrochloric acid hydrolyses of rice starch, waxy rice starch, corn starch and dassava starch were compared at acid concentraiton 0.7, 0.8, 0.9 and 1.0% for the first 2 starches and 0.2, 0.3, 0.4 and 0.5% for the last 2 starches. Hydrolysis conditions were starch 35%, temperature at 121°C, reaction time 15, 20, 25 and 30 min. Waxy rice starch was hydrolysed more than rice starch, and corn starch was hydrolysed more than cassava starch at the same acid concentration. Resulting in higher reducing agent and dextrose equivalent (DE) from waxy rice starch than from rice starch and higher from corn starch than from dassava starch at the same conditions. The maximum liquefied starch from rice starch and waxy rice starch was 91%, from corn starch and cassava starch was 98%. Compositons of small molecular weight saccharides (SMWA) (1-7 glucose units) from hydrolysis of 4 kinds of starch were the same, DP1 the highest, and the others were decreasing with the increasing glucose units. SMWS contents changed with DE, DP1 increased continually, while the others increased at first and decreased at high DE. At the same DE, waxy rice starch and corn starch and corn starch yielded the highest SMWS content, witch then gave the highest sweetness.